Articulação curricular entre a educação pré-escolar e o 1.º ciclo do ensino básico: conceções e práticas. - Cardoso, Ana Paula (2019)
Introduction: Curricular articulation between early childhood education and primary school is a fundamental process concerning the child’s adaptation to school. Primary teachers should establish links with pre-school educators, facilitating the transition between these two levels of education in a harmonious process, and promoting the continuity of the educational process. Objectives: To ascertain the importance and the meaning that teachers of primary school confer to curricular articulation and to know the aspects of the profile of the pupils that are favoured when consulting the individual process, as well as the most frequent initiatives regarding that articulation. Methods: A descriptive and analytical research was conducted, using a questionnaire survey applied to a sample of 45 teachers of the 1st year of primary school in the municipality of Viseu (Portugal). Results: From the data obtained, it is worth mentioning the great importance that teachers attribute to curricular articulation, the privilege conferred by them on how to behave in society (citizenship), the sense of autonomy and the children’s ability to communicate, as well as the teachers’ commitment to carry out a variety of activities and projects, in addition to the celebrations of thematic days and parties. Conclusion: Curricular articulation facilitates the transition between these two levels of education and contributes to an adequate adaptation of the children to the school, thereby promoting school success for all pupils.